FDR: fault detection and recovery scheme for wireless sensor networks using virtual grid. Issue 6 (2nd November 2017) - Singh, Kulwardhan; Sharma, T. P.
Abstract: Due to autonomous operation and constrained resources, nodes of a wireless sensor network are susceptible to failures. Due to multiple node failures, network topology may change or partition into many disconnected segments causing data/query path breakage. Early detection and recovery of faults is desirable in most scenarios. Also, due to limited battery life of a node, the solution must consume minimum possible energy for prolonged network operation. Hence in this paper, we propose a Fault Detection and Recovery scheme which is an energy efficient fault detection and recovery strategy that achieves minimum data loss by efficiently replacing faulty node on the present route or by finding full or partial alternate paths. Topology is managed by constructing a virtual grid over the entire network which helps in managing dynamically changing network topology easily and makes failure detection and recovery effective. It also helps to create energy efficient path between a source and a sink by finding shortest possible path. Further, nodes' cooperation is exploited to create certain zones on the data/query path which provides alternate nodes or possible alternate paths if required on some node failures. Thus, scheme achieves fault tolerance and at the same time achieves energy efficiency by always selecting shortest path for data delivery between source and sink. Analytical and simulation study reveals the significant improvement in terms of fault detection and energy conservation over existing similar schemes. Abstract : Fault Detection and Recovery (FDR) scheme using virtual grid which is an energy efficient fault detection and recovery strategy that achieves minimum data loss by efficiently replacing faulty node on the same route or by finding alternate (full or partial) path.